The consistory of the Church of Cadiz (14th-16th centuries): provisors, notaires and do- cumental praxis (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
In the Late Middle Ages, like the rest of the Hispanic and European dioceses, the Church of Cadiz had an office for the administration of ecclesiastical justice: the consistory. However, even though the Cadiz diocese traces its roots back to the Christian conquest of the city in the 13th century under the reign of Alfonso X the Wise, it wasn't until the end of the 14th century that the first documentary evidence of its functioning emerged. In this article, therefore, we will focus on the provisors who directed this office, as well as the notaries on whom they relied to formalize their scriptural needs.
Keywords: Consistory; provisor; documentary office; Cadiz; Middle Ages